Absence of Epidemiological Evidence on Anorexia Nervosa Among Adolescents in Pakistan - Muhammad Soban; Bisma Tariq (PKLI Journal of Health Sciences, 2026)
Anorexia nervosa is a severe psychiatric disorder associated with significant morbidity and elevated mortality risk. Despite its clinical importance, there is a striking lack of epidemiological evidence regarding its burden among adolescents in Pakistan. This letter highlights a critical literature gap identified during the conduct of a systematic review and meta-analysis that aimed to determine the prevalence and risk factors of anorexia nervosa in Pakistani adolescents. An extensive search of multiple electronic databases, complemented by hand searching and citation tracking, yielded insufficient eligible studies for meaningful synthesis. The absence of local data limits accurate estimation of disease burden, restricts context-specific prevention and management strategies, and compels reliance on evidence from high-income countries, which may not fully align with Pakistan’s sociocultural and healthcare realities. There is an urgent need for well-designed population-based and cross-sectional studies to generate robust national evidence to inform clinical practice, public health planning, and policy development tailored to Pakistan’s adolescent population.